THE ROLE OF ENTREPRENEURIAL ORIENTATION AND MARKETING PERFORMANCE IN MAINTAINING SUSTAINABLE COMPETITIVE ADVANTAGE IN COFFEE SHOPS IN MEDAN - Dona Tri Ardillah; Bunga Aditi; Sunaryo (RADJA PUBLIKA, 2025)
This research is motivated by the rapid growth of coffee shops in Medan, which has also shown changes in consumer preferences. This rapid growth has led to problems arising from increasing customer demand and declining customer satisfaction, resulting in some coffee shops being unable to meet consumer expectations. This study aims to analyze the influence of entrepreneurial orientation and marketing performance on maintaining sustainable competitive advantage in the growing coffee shop industry. The research method used was descriptive quantitative, with data collected through questionnaires distributed to 100 business owners, out of a total population of 650 coffee shops in Medan. The results indicate that entrepreneurial orientation and marketing performance have a significant influence on sustainable competitive advantage. Multiple linear regression was used to examine the relationship between the variables. This research is expected to provide insights for business owners in formulating appropriate strategies to increase competitiveness in an increasingly competitive market.